Love as the Fundamental Dynamics of Family Upbringing according to Chiara Lubich. Selected Aspects - Kozubek, Mariola Teresa (Paedagogia Christiana, 2019)
Civilisational progress and globalisation processes at the turn of the 20th and 21st centuries have changed the shape, function and role of family in social life, posing a threat to its stability. Consequently, many family support institutions and organisations are created that offer social services focused on prevention, family therapy and support, particularly in terms of family upbringing. In search of a model of family upbringing that teaches how to build long-term interpersonal relationships and overcome difficulties by referring to values helpful in dealing with family crises, the article focuses on the pedagogical potential of contemporary movements and communities of the Catholic Church. Substantial studies in this regard are provided by the New Families Movement, an initiative that operates under the international Focolare Movement founded by the Italian teacher Chiara Lubich (1920–2008). Based on the hermeneutics of Lubich’s texts, the article presents her main thoughts on family upbringing. Following the adopted research procedure, the text discusses the significance of personal love from the philosophical, psychological and theological perspective as well as through life and educational experience of Chiara Lubich and her anthropological and theological reflections on education. In this context, several key aspects of family upbringing are discussed in the context of personal love: parental authority and responsibilities, specificity of integral education, characteristics of pro-social education and development of skills necessary to overcome difficulties. They appear to be a fundamental part in Lubich’s ‘style’ of family upbringing. The resulting analysis belongs to the field of family pedagogy and pedagogy of religion, and is mostly based on Italian literature sources. Chiara Lubich’s pedagogical thought is not well-known in Polish pedagogical literature, which makes it all the more compelling to address this topic.